Characteristics of Cholelithiasis Patients in Dr. Achmad Mochtar General Hospital Bukittinggi on January 2019 - December 2020 - Muhammad Reza Azriyantha; Ambiar Manjas (HM Publisher, 2022)
Background. Cholelithiasis is a condition where there are stones in the gallbladder or the common bile duct or both. This study aims to describe the characteristics of cholelithiasis patients in RSUD Dr. Achmad Mochtar Bukittinggi. Methods. This research is a descriptive observational study on the incidence of cholelithiasis in hospitals. Dr. Achmad Mochtar Bukittinggi period January 2019 – December 2020. A total of 224 research subjects participated in this study. Secondary data was collected from medical records of research subjects, including data on age, gender, body mass index, clinical symptoms, and type of surgery. Data analysis was carried out with the help of SPSS 25 software. Results. Cholelithiasis was most commonly found in the age group over 50 years (47.8%), normal BMI (46%) cases. The most complained symptom in cholelithiasis patients in this study was abdominal pain (61.6%). All cholelithiasis patients (100%) in this study underwent laparoscopic cholecystectomy surgery. Conclusion. Cholelithiasis patients who underwent surgery in hospitals. Dr. Achmad Mochtar Bukittinggi for the period January 2019 – December 2020 were 224 patients. The majority of patients over 50 years of age, women, had a normal BMI. The patient frequently complained of abdominal pain and all had undergone laparoscopic cholecystectomy.